2016
DOI: 10.1007/s40617-016-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequently Assigned Readings in Behavior Analysis Graduate Training Programs

Abstract: Demand for behavior-analytic services has greatly increased in recent years, resulting in the development of many new graduate training programs. The purpose of the present study was to identify frequently assigned readings from the course syllabi of behavior-analytic training programs with the highest pass rates on the Board Certified Behavior Analyst® (BCBA®) examination. The readings are categorized by curriculum area (e.g., ethics, behaviorism, singlesubject research methodology) to provide a resource for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Both the JEAB and JABA editorial boards recognized Skinner's writings, as well as research-methods texts (e.g., Johnston & Pennypacker, 1993;Sidman, 1960), as "essential" (listed by at least 25% of participants of the survey), supporting the aforementioned viewpoint described by Sidman (2011). Although this analysis had a heavier emphasis on EAB compared to the one conducted by Pastrana et al (2016), it is unclear whether the nominations of editorial board members align with the curricular decisions being made by current training programs. Thus, one way to extend the analyses of both Pastrana et al (2016) and Saville et al (2002) is to survey the syllabi of programs that explicitly incorporate EAB into a curriculum for emerging scientist-practitioners.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Both the JEAB and JABA editorial boards recognized Skinner's writings, as well as research-methods texts (e.g., Johnston & Pennypacker, 1993;Sidman, 1960), as "essential" (listed by at least 25% of participants of the survey), supporting the aforementioned viewpoint described by Sidman (2011). Although this analysis had a heavier emphasis on EAB compared to the one conducted by Pastrana et al (2016), it is unclear whether the nominations of editorial board members align with the curricular decisions being made by current training programs. Thus, one way to extend the analyses of both Pastrana et al (2016) and Saville et al (2002) is to survey the syllabi of programs that explicitly incorporate EAB into a curriculum for emerging scientist-practitioners.…”
mentioning
confidence: 58%
“…Furthermore, there was much variability among the sample of syllabi with regard to the total number of assigned readings, which means syllabi with higher reading counts are more represented in our data. Therefore, similar to Pastrana et al (2016), who only included 20 institutions with BACB verified course sequences in their analyses, we advise readers looking to develop syllabi or curricula to utilize our findings as one resource among more comprehensive strategies for selecting content and assigned readings. Currently there is no objective method to determine what should and should not be taught in an EAB course; therefore, our findings are just descriptive and not prescriptive.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…On the education front, we should strive to incorporate the aforementioned information into all verified course sequences and emphasize how critical it is to all applied behavior analysts. A recent survey of a select group of graduate training programs revealed that the most frequently assigned readings on verbal behavior were focused on topics related to Skinner's elementary verbal operants (Pastrana et al, 2018). This is a good starting point; however, graduate training programs should consider incorporating portions of seminal readings (Skinner, 1957), as well as readings on more advanced topics in verbal behavior (Hayes et al, 2001;Sidman, 1994), even if no one course is solely dedicated to this topic.…”
Section: The Applied Research-to-practice Gapmentioning
confidence: 99%